Analisis Hubungan Antara Jalur Masuk Universitas dengan Predikat Kelulusan Mahasiswa - Kamila, Yasmin; Sa’idah, Andini; Akbar, Aditya Syarifudin; Azzen, Fiyadika Amalia Nurizah; Rohim, Achmad Yazid Busthomi; Chamidah, Nur (Zeta - Math Journal, 2023)
There are different characteristics of each entry route, so there will be the potential to achieve a different GPA. There are 3 types of entrance routes for public universities held by LTMPT, namely SNMPTN, SBMPTN, and SMMPTM. The achievement of student learning outcomes in tertiary institutions can be seen through the final results indicated by the GPA. Diploma and undergraduate program students have four graduation predicates, three of which are satisfactory (GPA 2.76-3.00), very satisfactory (GPA 3.01-3.50), and with honors (GPA more than 3.50). The population in this study were all PTN graduates from 2018 to 2022. The sample used in this study was at least 50 PTN graduates from 2018 to 2022 and 150 samples. This research will be tested using the Chi-Square test method. Based on the Chi-Square test on the contingency table related to the relationship between college admissions and student graduation predicates, it can be concluded that there is no relationship between college admissions and student graduation predicates. In addition, the relationship between university admissions and student graduation predicates is related to majors and campus clustering in 2020. Meanwhile, the relationship between university admissions and student graduation predicates has no relationship with gender and domicile.